Perforation of the ileum due to Crohn's disease in a teenager without previous diarrhea: case report - López Claros, Jorge (2022)
Crohn disease is of immunological origin, in which an inflammatory condition occurs that can be located anywhere in the intestine, especially in the ileocecal part. It is usually characterized by diarrhea and pain with weight loss. The present case is of a 15-year-old girl who abruptly debuts with abdominal right iliac fossa (RIF) pain, which suggests an appendicular condition, so she underwent surgery. In later days, he presented persistent vomiting, suspected of an obstructive condition. A second surgical intervention shows an inflammatory condition at the ileocecal level, so a colostomy and ileostomy are performed. Biopsy showed lesions consistent with Crohn's disease. Treatment with mesalazine and azathioprine was performed, achieving a remission of the picture. Six months later an anastomosis was performed with a favorable evolution of the patient.